A clinical study on maternal and fetal outcomes of obstructed labour - Dulewad, Shirish S.; Gupta, Priyanka K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Obstructed labour is the failure of the fetal presenting part to descend in the birth canal despite adequate uterine contractions. This study aims to identify risk factors for obstructed labour and highlight strategies to reduce maternal and fetal morbidity and mortality. Methods: This prospective cross-sectional study included all women with prolonged and obstructed labour at a tertiary hospital. Complete enumeration was used for sampling, and data were analysed using Microsoft excel. Results: A total 48 patients were of the age of 18-25 years. 78 were primigravida. 32 patients needed operative vaginal delivery. In postpartum complications, 26 patients went into atonic PPH, 1 underwent laparotomy for rupture uterus,18 patients had extension of the uterine incision during LSCS and 8 patients suffered from vaginal lacerations. Postpartum complications such as anemia found in 34 cases, sepsis in 26 cases, paralytic ileus in 28 cases and surgical site infection in 12 patients. 21 patients had prolonged hospital stay. 8 babies died, 19 babies were still admitted in NICU and 75 were healthy. Conclusions: Regular antenatal visits and pelvic evaluation beyond 37 weeks by an experienced gynaecologist are essential for diagnosing adequacy. Attendants at rural centres must be trained to monitor labour and identify prolonged labour using a partograph. Most obstructed labour cases are preventable if pregnant women receive proper antenatal care, births are attended by trained personnel, uterotonics are used appropriately, and instrumental vaginal deliveries are performed by expert gynaecologists when indicated.